Establishing a peer advisory board in a mental health ethics research group – challenges, benefits, facilitators and lessons learned - Faissner, Mirjam; Braun, Esther; Efkemann, Simone Agnes; Gaillard, Anne-Sophie; Haferkemper, Iris; Hempeler, Christin; Heuer, Imke; Lux, Ursula; Potthoff, Sarah; Scholten, Matthé; Spiegel, Sylvia; Stefaniak, Christina; et al. (Frontiers in Psychiatry, 2025)
While participatory methods are regarded as beneficial in many areas of psychiatric research, they are still rarely considered in the field of mental health ethics. Yet, there are several epistemic and ethical reasons why participatory research is particularly important in this field, such as the high relevance of experiential knowledge for ethical analyses. In this article, we report our experiences with establishing a peer advisory board for an existing mental health ethics research group. We demonstrate how a peer advisory board can provide low-threshold opportunities for various forms of participation, which can occur simultaneously within one research project. We first describe how we established the peer advisory board and explain its structure. We then give an overview of several research projects that involved various forms of participation by members of the peer advisory board, such as the development of a template for a psychiatric advance directive, the co-writing of articles, and the organization of scientific events. We discuss the challenges, benefits, and facilitators of a peer advisory board from our different vantage points as service users, relatives, clinicians, and researchers. Challenges included organizational barriers such as time constraints and rigid bureaucratic structures within academic institutions and funding bodies as well as the persistence of power imbalances between members of the research group and the peer advisory board. Benefits included the opportunity for personal development and capacity building among both peer advisory board members and members of the research group, and the multiplication of research results among the relevant communities. Based on a reflection on our own experiences, we argue that participatory research in mental health ethics is not only ethically and epistemically desirable but also practically feasible. We close by formulating several lessons learned from our experiences.